Magic words or talking point? The framing of 'radical Islam' in news coverage and its effects. (April 2021) - Hoewe, Jennifer; Bowe, Brian J.
This study examines the use of the term 'radical Islam' as a framing device from two perspectives. First, a content analysis of The New York Times and Washington Post suggested that 'radical Islam' is a recent addition to the public lexicon and is rapidly rising in use. The term is more recently associated with negatively charged language and linked to terrorism. Second, an experiment showed that reading about a perpetrator associated with 'radical Islam' (as opposed to 'terrorism') led to an increase in Islamophobia among all participants – indicated through fear of Muslims and Islam. An interaction effect emerged such that self-identified conservatives did not differentiate between 'radical Islam' and 'terrorism' when determining culpability, but self-identified liberals did. These results indicate that the US news media has increasingly linked 'radical Islam' with terrorism and other negative ideas, while some sectors of the American public struggle to disentangle the two concepts.